Алгоритм організації віддаленого доступу до захищеного сегменту корпоративних комп’ютерних мереж - Чепурна, І. С. (ХНУРЕ, 2024)
The article considers the application of remote client access in corporate networks using VPN tunneling based on the Proxmox virtual environment. The problem of secure connection of remote users with the internal network of the enterprise through the use of virtualization and VPN technologies is investigated. Emphasis is placed on analyzing the effectiveness of using Proxmox virtualization technology to create secure connections and ensure secure access of remote users to corporate resources. The advantages of using Proxmox-based VPN tunneling in the context of ensuring confidentiality, integrity and availability of data in corporate networks are discussed.
Keywords: організація віддаленого доступу; корпоративна комп’ютерна мережа